Qualitative analysis of the menu preparations of an institution supporting people with disabilities (Research, Society and Development, 2022)
Objective: The scope of this study is to qualitatively evaluate the menu of a meal offered to students of na institution supporting people with disabilities in the city of Teresina, Piauí. Methodology: This is a field study, with a descriptive, qualitative and cross-sectional design, which evaluated the five-week lunch menu of an institution supporting people with disabilities. The menus were evaluated using the adapted AQPC method. The aspects: i) positive and ii) negative, were classified as “excellent”, “good”, “regular”, “bad” and “very bad”. Results: i) it was classified as “good” for the absence of ultra-processed foods (84%) and the use of in natura foods (84%); “bad” for hardwoods (40%) and “terrible” for fruits (0%). ii) it was classified as “great” for the variety of colors in the preparations (0%), industrialized sweets (0%) and cooking methods (0%); “good” for sausages (16%); “regular” for frying (32%) and for sulfur (32%) and “poor” for products with sugar or added (80%). Conclusion: The results of the evaluation of the menu indicate a significant supply of fresh food, a variety of colors in the meals and a low supply of sausages in the preparations served at the institution for students on a daily basis, which is considered a positive point. On the other hand, the regularity of fried foods, the frequency of foods containing sulfur and products with added sugar point to the need for adjustments in the menu to improve the nutritional and sensory aspects of the preparations offered to diners.